Presentation and Outcome of Management of Parotid Tumors: A Local Experience from Two Sudanese States - E E Salah, Sami; E Mohammed, Sami Galal-eldin; Elmushly, Rehab (Gezira Journal of Health Sciences, 2015)
Parotid tumors are rare but good amount of knowledge is required to preserve the facial nerve during   superficial or deep parotidectomy.  This is a study of 49 patients   who presented with parotid tumors in the last 12 year with a mean age of 44 yrs. Parotid lump was the main symptom in all patients, while facial nerve palsy was the presenting symptom in only 4.1%. In this study 69.3% of patients   underwent superficial parotidectomy while 30.6% had total parotidectomy. Transient facial nerve palsy occurred in   22.4% while permanent damage occurred in (8.1%) of patients. Pleomorphic adenoma represented 91.8% of benign tumors while mucoepidermoid tumors represented 41.6% of malignant tumors making them the two most common pathological diagnoses. Recurrence occurred in only 3 patients